BILATERAL INTERPRETING COURSE IN BLENDED LEARNING: EXPERIMENTAL VERIFICATION - Svitlana Kolomieets; Lyudmyla Guryeyeva (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The paper presents the research on the effectiveness of blended learning within the designed Moodle-based course of bilateral interpreting using interdisciplinary terminology. The authors analyse modern educational technologies and prospects for future professionals in the context of bilateral interpreting. The research reveals the outcomes of the experimental study conducted at the National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute" involving the students at the final stage of the bachelor's degree programme proving the efficiency of modern approach based on blended learning concept. The study also proves the fact that integration of blended learning courses can help future professionals develop skills such as critical thinking, problem solving, agility and adaptability, initiative and entrepreneurialism, effective oral and written communication, accessing and analysing information that are considered to be critically important for the twenty-first century. The detailed analysis of modern scientific literature proves that modern information technologies and blended learning, in particular, become an integral part of today's educational tendencies both in Ukraine and abroad, offering a wide range of possibilities for students.